Autoeficácia docente e escolha pelo ensino superior no contexto do estágio de docência em engenharia - Matos, Mayara da Mota [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims to describe and analyze the relations between the beliefs on self-efficacy and the factors that lead to choose the teaching career in college education in the context of the teaching traineeship in engineering field. In order to find answers for the following questions: How the teaching traineeship influences the engineering graduate students' beliefs of self-efficacy?; Which factors influence the choice of these graduate students for the teaching career? and, Are self-efficacy beliefs related to the choice for college education teaching career? We have delimited as specific objectives: to characterize the student's profile in graduate engineering programs; to measure the level of teacher self-efficacy and the sources of formation of this belief in the context of the teaching traineeship; to identify factors that lead students in these graduate programs to choose being teachers in college education and to correlate the described variables above with the teaching traineeship in Engineering courses. Therefore, we have made use of four search tools, namely: a socio-demographic survey questionnaire, a Teacher Self-efficacy Scale (TES), developed by Polydoro et al. (2004), a Self-efficacy Teachers Sources scale (IAOCHITE; AZZI, 2012) and the free translation into Portuguese and adaptation of Factors Influencing Choice Teaching - FIT - Choice Scale, proposed by Watt, Richardson (2007), who named it as Scale of Factors that influence the choice for teaching. The results indicated that the participants have beliefs of moderate auto-efficacy, with a mean score of 4.46 (SD = 0.69). The average was higher in Intentionality dimension of teaching activities (M = 4.51, SD = 0.70) than in Classroom Management (M = 4.40, SD = 0.72). The sources of information of the most influential Self-efficacy beliefs were, respectively, social persuasion, direct experiences and vicarious experiences, which positively influenced ...

O presente estudo teve como objetivos descrever e analisar as relações entre as crenças de autoeficácia e os fatores que levam à escolha pela docência no Ensino Superior no contexto do Estágio de docência no campo da engenharia. Visando responder às questões De que maneira o estágio de docência influencia as crenças de autoeficácia dos pós-graduandos em engenharia?; Quais os fatores que influenciam na escolha desses pós-graduandos pelo ensino? e, As crenças de autoeficácia estão relacionadas à sua escolha pelo Ensino Superior?. Delimitou-se como objetivos específicos: caracterizar o perfil do estudante em programas de pósgraduação de Engenharia; mensurar o nível de autoeficácia docente e as fontes de constituição dessa crença no contexto do estágio de docência; identificar fatores que levam esses discentes a escolherem serem docentes em nível superior e, correlacionar as variáveis acima descritas com o estágio de docência nos cursos de Engenharia. Para tanto, a partir de um estudo de natureza quantitativa, utilizou-se quatro instrumentos de pesquisa, a saber: um questionário sociodemográfico, a Escala de Autoeficácia de Professores (EAD), desenvolvida por Polydoro et al. (2004), a Escala de Fontes de Autoeficácia de Docentes (IAOCHITE; AZZI, 2012) e a tradução livre para o português e adaptação da Factors Influencing Teaching Choice - FIT - Choice Scale, proposta por Watt, Richardson (2007) a qual denominou-se Escala de Fatores que Influenciam a Escolha pelo Ensino (EFIEE). Os resultados indicaram que os participantes possuem crenças de autoeficácia moderadas, com escore médio de 4,46 (DP=0,69). A média foi maior na dimensão Intencionalidade da ação docente (M= 4,51; DP=0,70) do que na Manejo em sala de aula (M=4,40; DP=0,72). As fontes de informação das crenças de autoeficácia mais influentes foram, respectivamente, a persuasão social, as experiências diretas e as...
Keywords: Teachers, Training of; Professores - Formação; Engenharia; Auto-eficácia; Professores - Estágios; Estagiarios (Educação)